Analysis of glomerular PLA2R efficacy in evaluating the prognosis of idiopathic membranous nephropathy in the background of different serum anti-PLA2R levels. Issue 1 (31st December 2022) - Sun, Yuemeng; Lan, Ping; Feng, Jie; Wang, Zhigang; Liu, Chao; Xie, Liyi; Yu, Xiaoyang
Abstract: Objective: To verify glomerular PLA2R antigen and serum PLA2R antibody expression in membranous nephropathy as well as to explore glomerular PLA2R efficacy in evaluating the prognosis of idiopathic membranous nephropathy (IMN) in the background of different serum anti-PLA2R levels. Methods: We retrospectively analyzed 155 patients who were diagnosed with IMN by kidney biopsy. Patients were divided into six groups according to their serum PLA2R antibody or glomerular PLA2R antigen positiveness and the level of serum anti-PLA2R titer. Both clinical features and pathological characteristics were recorded, and the remission time was compared among groups. Correlation between clinical figures and the anti-PLA2R titer or semi-quantity of glomerular PLA2R antigen was detected. Results: A positive correlation between time to partial remission and serum anti-PLA2R titer was found. Among patients with serum anti-PLA2R titer <150 RU/ml, there were shorter remission time in negative glomerular PLA2R antigen group compared with positive glomerular PLA2R antigen, and a positive correlation between time to complete remission and semi-quantity of glomerular PLA2R antigen was found. Conclusion: Both glomerular PLA2R antigen and serum anti-PLA2R play a role in disease presentation and prognosis in primary membranous nephropathy. Glomerular PLA2R antigen has a major role on disease prognosis when serum anti-PLA2R titer is less than 150RU/ml, while serum anti-PLA2R has predominant role in IMN prognosis when serum anti-PLA2R titer is above 150RU/ml.